Toward a Harmonized Future: Regional Innovation Systems, Global Standards, and the Path to Sustainable Development - Jacob, Daniel Etim; Jacob , Imaobong Daniel (Standards-related Regional Innovation and International Cooperation, 2025)
Fragmentation between Regional Innovation Systems (RIS) and Global Standardization Frameworks (GSF) presents a critical barrier to advancing sustainable development, technological diffusion, and coherent international policy coordination. This paper investigates how harmonization between RIS and GSF can catalyze innovation while also addressing the risks of lock-in, inequity, and fragmentation. Drawing on a conceptual and narrative review, we develop a conceptual framework that positions standardization as both an enabler and constraint of innovation. Our analysis is guided by three dimensions: the tension between localized innovation and global uniformity, the role of standards as mediating mechanisms for diffusion and legitimacy, and the challenges of polycentric governance and path dependency. Through critical synthesis, the paper argues that standardization reduces uncertainty, scales markets, and facilitates knowledge transfer, but also risks privileging dominant actors and excluding local contexts. Polycentric governance emerges as the key solution, offering a pathway to reconcile regional diversity with the universality of global rules. The primary contribution is the proposal of a novel Comparative Framework and Key Performance Indicators (KPIs) designed to systematically evaluate harmonization outcomes, addressing the critical gap in current innovation policy literature. We conclude that by reframing harmonization as a dynamic, iterative process rather than a fixed institutional goal, the paper highlights pathways for aligning innovation systems with global sustainability imperatives. The findings contribute to theory-building on innovation governance and provide insights for policy frameworks navigating technological and environmental transitions.